FRI0035 Specific monocyte subsets in patients with rheumatoid arthritis are associated with the progression of the disease along with their autoimmune and pro-atherothrombotic profile. (15th June 2017) - Barbarroja, N; Ruiz-Limon, P; Pérez-Sánchez, C; Jimenez-Gomez, Y; Abalos, MC; Segui, P; Ortega, R; Collantes, E; Escudero, A; Alarcon-Riquelme, M; Lelann, L; Jamin, C; et al.
Abstract : Background: Circulating monocytes play a key role in the pathogenesis of cardiovascular disease (CVD). Three monocyte subsets have been described based on their CD14 and CD16 expression profiles, with different actions in vascular pathology. The distribution of these monocyte subsets and their inflammatory profile associated with CVD in rheumatoid arthritis (RA) remain unknown. Objectives: This study, developed within the Innovative Medicines Initiative Joint Undertaking (IMI JU) project PRECISESADS framework, aimed at: 1) determine which of the two CD16+ monocyte subpopulations is expanded in RA patients and to investigate their possible role in disease pathogenesis. 2) Functionally characterize the CD16+ monocyte subsets in RA patients and analyze their role in the pro-atherothrombotic profile associated to RA. Methods: The frequencies of monocyte subpopulations in the peripheral blood of 50 healthy donors and 50 RA patients included in the PRECISESADS study were determined by flow cytometry. A second cohort of 30 RA patients was included, of which CD16+ monocyte subpopulation was isolated using immuno-magnetic selection. Proinflammatory circulating cytokines, as well as peroxide levels and cellular activation markers were analyzed. The expression of 84 genes related to atherosclerosis was analyzed by PCR-array. Endothelial function was measured through post occlusive hyperaemia using Laser-Doppler. Carotid intima media thickness (CIMT) was evaluated as atherosclerosis marker. Results: CD14highCD16+ monocyte subset was expanded in RA patients belonging to the PRECISESADS study. Their frequency correlated with the evolution of the disease as well as with the positivity for RF and anti-CCP autoantibodies. Correlation studies further indicated a link between the increased frequency of these monocytes and increased levels of circulating cytokines such as IL-17F and IL-10. CD14highCD16+ monocytes were also significantly extended in RA patients of the second cohort. Those patients had impaired endothelial function, with a reduced perfusion value after ischemia. Increased CD14highCD16+ monocyte proportions were associated with both endothelial dysfunction and the presence of a pathologic CIMT. CD16+ monocyte subsets showed increased protein and gene expression of proinflammatory cytokines, markers of atherosclerosis and peroxide levels. Conclusions: RA patients exhibit an increased number of CD14highCD16+ monocytes, which display a specific atherogenic and inflammatory pattern directly associated to the autoimmune profile, the progression of the disease and the altered microvascular function. That data suggest that CD16+ subpopulation might play a key role in the CVD pathogenesis associated with RA. Acknowledgements: Supported by the Innovative Medicines Initiative Joint Undertaking under grant agreement n°115565, resources of which are composed of financial contribution from the European Union's Seventh Framework Programme (FP7/2007–2013) and EFPIA companies' in kind contribution, the Instituto de Salud Carlos III (FIS PI15/1333; RIER Rd16/0012/0015) and the JA (CTS-7940). Disclosure of Interest: None declared